2006
DOI: 10.1079/asc200636
|View full text |Cite
|
Sign up to set email alerts
|

A partial genome scan to map quantitative trait loci for carcass composition, as assessed by X-ray computer tomography, and meat quality traits in Scottish Blackface Sheep

Abstract: Quantitative trait loci (QTL) were identified for traits related to carcass and meat quality in Scottish Blackface sheep. The population studied was a double backcross between lines of sheep divergently selected for carcass lean content (LEAN and FAT lines), comprising nine half-sib families. Carcass composition (600 lambs) was assessed non-destructively using computerized tomography (CT) scanning and meat quality measurements (initial and final pH of m. semimembranosus, colour, shear force value, carcass weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 38 publications
0
21
0
1
Order By: Relevance
“…Nematode resistance loci in sheep V Riggio et al definitions (for example, Walling et al, 2004;McRae et al, 2005;Karamichou et al, 2006;Raadsma et al, 2009;Jonas et al, 2010). However, Hadjipavlou and Bishop (2008) have shown that body weight QTL changes over time in Scottish Blackface sheep.…”
Section: Discussionmentioning
confidence: 99%
“…Nematode resistance loci in sheep V Riggio et al definitions (for example, Walling et al, 2004;McRae et al, 2005;Karamichou et al, 2006;Raadsma et al, 2009;Jonas et al, 2010). However, Hadjipavlou and Bishop (2008) have shown that body weight QTL changes over time in Scottish Blackface sheep.…”
Section: Discussionmentioning
confidence: 99%
“…CT scanning, which is currently being used in sheep breeding programs for the evaluation of carcass quality, could also provide the means to select on MQ traits. In two different studies (Karamichou et al, 2006;Navajas et al, 2006a), live CT measurements have been reported to predict MQ traits with moderate accuracy, most likely due to the associations between IMF and CT-measured muscle density. Karamichou et al (2006) reported significant phenotypic and genetic correlations between CT and meat eating quality traits, and Navajas et al (2006a) also found strong associations between CT muscle density and IMF.…”
Section: --mentioning
confidence: 99%
“…A small proportion of reciprocal LEAN 3 FAT line crosses were made at the 1999 matings, so that a cohort of F 1 lambs were born in April 2000 along with a majority of purebred LEAN and FAT line lambs. The male F 1 lambs were then backcrossed to the purebred LEAN and FAT line ewes to create a population of F 1 3 LEAN and F 1 3 FAT lambs from 2001 to 2003, for the purpose of QTL detection (Karamichou et al, 2006b and2006c). A small number of F 1 3 (F 1 3 LEAN) and F 1 3 (F 1 3 FAT) were born in 2003 when female backcross lambs from 2001 themselves became dams.…”
Section: Animalsmentioning
confidence: 99%